2022
DOI: 10.3390/ijms231911585
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Environment-Responsive Alternative Splicing in the Inflorescences of Cultivated and Wild Tomato Species

Abstract: Cultivated tomato (Solanum lycopersicum) is bred for fruit production in optimized environments, in contrast to harsh environments where their ancestral relatives thrive. The process of domestication and breeding has profound impacts on the phenotypic plasticity of plant development and the stress response. Notably, the alternative splicing (AS) of precursor message RNA (pre-mRNA), which is one of the major factors contributing to transcriptome complexity, is responsive to developmental cues and environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In grapevines, alternative splicing has been linked to phenotypic specificities and distinct adaptive capacities by enabling a diverse range of proteins to be produced [ 63 ]. Several studies suggest that crop domestication has selected alternative splicing variation linked to desired traits, such as flower production [ 64 ], anthocyanin accumulation [ 65 ] or cell wall degradation in fruits [ 66 ]. Research highlighted in a study on pear ( Pyrus pyrifolia ) revealed how domestication has led to changes in the alternative splicing of genes that contribute to the fruit traits such as sugar metabolism, acid metabolism, stone cell formation, and fruit firmness [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In grapevines, alternative splicing has been linked to phenotypic specificities and distinct adaptive capacities by enabling a diverse range of proteins to be produced [ 63 ]. Several studies suggest that crop domestication has selected alternative splicing variation linked to desired traits, such as flower production [ 64 ], anthocyanin accumulation [ 65 ] or cell wall degradation in fruits [ 66 ]. Research highlighted in a study on pear ( Pyrus pyrifolia ) revealed how domestication has led to changes in the alternative splicing of genes that contribute to the fruit traits such as sugar metabolism, acid metabolism, stone cell formation, and fruit firmness [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research highlighted in a study on pear ( Pyrus pyrifolia ) revealed how domestication has led to changes in the alternative splicing of genes that contribute to the fruit traits such as sugar metabolism, acid metabolism, stone cell formation, and fruit firmness [ 66 ]. Similarly, comparative analyses between wild and cultivated tomato species have shown that domestication impacts environment-responsive alternative splicing in the inflorescences, suggesting a role in adaptability and phenotypic diversity [ 64 ]. In the spiny Solanum group, a study identified a DFR gene where alternative splicing, influenced by a natural promoter variant, plays a crucial role in anthocyanin accumulation, a trait selectively enhanced during domestication [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In tomato, around 65% of the annotated protein-coding genes possess multiple transcript isoforms ( Clark et al., 2019 ). Alternative splicing changes have been reported in tomato plants grown under phytotron vs greenhouse conditions ( Wang et al., 2017 ), in inflorescences of cultivated and wild tomato species ( Zhou et al., 2022 ), during fruit development regulation ( Sun and Xiao, 2015 ; Wang et al., 2016 ), pollen responses to heat stress ( Keller et al., 2017 ), tomato responses to drought stress ( Lee et al., 2020 ), water deficit stress ( Ruggiero et al., 2022 ), low nitrate stress ( Ruggiero et al., 2022 ), phosphate starvation ( Tian et al., 2021 ), and response to the fungal infection by Trichoderma harzianum ( De Palma et al., 2019 ). Based on these studies, differential alternative splicing (DAS) was found to be tissue-specific, developmental stage-related or stress-responsive condition.…”
Section: Discussionmentioning
confidence: 99%
“…In tomato, around 65% of the annotated protein-coding genes possess multiple transcript isoforms (Clark et al, 2019). Alternative splicing changes have been reported in tomato plants grown under phytotron vs greenhouse conditions (Wang et al, 2017), in inflorescences of cultivated and wild tomato species (Zhou et al, 2022), during fruit development regulation (Sun and Xiao, 2015;Wang et al, 2016), pollen responses to heat stress (Keller et al, 2017), tomato responses to drought stress (Lee et al, 2020), water deficit stress (Ruggiero et al, 2022), low nitrate stress (Ruggiero et al, 2022), phosphate starvation (Tian et al, 2021), and response to the fungal infection by Trichoderma harzianum (De Palma et al, 2019). Based on these studies, differential alternative splicing (DAS) was found to be tissuespecific, developmental stage-related or stress-responsive condition.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, RI event was reported to be the most frequent event induced by salt stress in Arabidiopsis (Ding et al, 2014b), wheat (Liu et al, 2018), cotton (Zhu et al, 2018) and Barley (Fu et al, 2019), while A3SS was the mostly affected AS events in rice by salt stress (Fu et al, 2019). Given that the differences in AS profiles are related to tissue type, stress condition and genotype (Gan et al, 2011;Vitulo et al, 2014;Martıń et al, 2021;Zhou et al, 2022), the differences on the alternative splicing preference induced by salt may contribute to the evolutionary adaptation process in tomato.…”
Section: Discussionmentioning
confidence: 99%